2004
DOI: 10.1189/jlb.0504300
|View full text |Cite
|
Sign up to set email alerts
|

Stabilin-1 localizes to endosomes and the trans-Golgi network in human macrophages and interacts with GGA adaptors

Abstract: Stabilin-1 and stabilin-2 constitute a novel family of fasciclin domain-containing hyaluronan receptor homologues recently described by us. Whereas stabilin-1 is expressed in sinusoidal endothelial cells and in macrophages in vivo, stabilin-2 is absent from the latter. In the present study, we analyzed the subcellular distribution of stabilin-1 in primary human macrophages. Using flow cytometry, expression of stabilin-1 was demonstrated on the surface of interleukin-4/dexamethasone-stimulated macrophages (MPhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 62 publications
3
100
1
1
Order By: Relevance
“…The other genes of interest involved in the vesicular pathways that were upregulated were VPS54, required for retrograde transport of Golgi membrane proteins from endosomal compartments and synapsin II which in involved in post-trans-Golgi trafficking pathways (Bustos et al, 2001, Maienschein et al, 1999Conibear and Stevens, 2000). Additionally the genes, stabilin-1, Rab6B, and the adaptor complex, AP-1, which are all involved in vesicular trafficking from the Golgi to the endosomes, were all down regulated (Kzhyshkowska et al, 2004;Opdam et al, 2000;Robinson, 2004). Thus although the effect on vesicular trafficking found in this study was modest, collectively these genes do suggest that in astrocytes IFN-γ may affect genes that are involved in regulation of membrane trafficking events in the vesicular trafficking pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The other genes of interest involved in the vesicular pathways that were upregulated were VPS54, required for retrograde transport of Golgi membrane proteins from endosomal compartments and synapsin II which in involved in post-trans-Golgi trafficking pathways (Bustos et al, 2001, Maienschein et al, 1999Conibear and Stevens, 2000). Additionally the genes, stabilin-1, Rab6B, and the adaptor complex, AP-1, which are all involved in vesicular trafficking from the Golgi to the endosomes, were all down regulated (Kzhyshkowska et al, 2004;Opdam et al, 2000;Robinson, 2004). Thus although the effect on vesicular trafficking found in this study was modest, collectively these genes do suggest that in astrocytes IFN-γ may affect genes that are involved in regulation of membrane trafficking events in the vesicular trafficking pathway.…”
Section: Discussionmentioning
confidence: 99%
“…STAB1 (signal transducer and activator of transduction 3), a multifunctional glycoprotein, was shown to be cardioprotective [Wang et al, 2009b]. It has been known that as a scavenger receptor, STAB1 recognizes acetylated lowdensity lipoproteins that can bind to macrophages playing a role in clearance and interacting with a variety of growth factors in angiogenesis [Adachi and Tsujimoto, 2002;Kzhyshkowska et al, 2004;Salmi et al, 2004]. The present research revealed that in blood samples at an early stage of AMI, STAB1 was significantly upregulated in healthy and stable coronary arteries at the first day of discharge; whereas it showed no difference in samples after 6 months of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] Cells were fi xed for 10 min with 2% paraformaldehyde (PFA) in PBS, permeabilized for 15 min with 0.5% Triton X-100 in PBS, and followed by another 10 min fi xation with 4% PFA in PBS. Samples were blocked with 3% bovine serum albumin (BSA) in PBS for 1 h. Samples were incubated for 1 h and 30 min with primary antibodies followed by several 5 min washing steps with PBS.…”
Section: Methodsmentioning
confidence: 99%